Analisis Dampak dan Potensi Pengembangan Gastronomi Pada Kawasan Kepulauan Seribu - Reza Ardian Putra; Christoper Prajevon; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is about the Thousand Islands Park in Jakarta with the aim of developing Thousand Islands tourism and determining the unique culinary delights of the Thousand Islands as gastronomy. Gastronomy as a sector seeks to attract significant global attention. It is known that the number of tourists who want to enjoy a different special culinary experience continues to increase from time to time. This research method uses the library research or literature review method. From this study it was concluded that the development of the islands in the Thousand Islands tourist park is very lacking because it is often constrained by the availability of small water resources. While the typical food is the atomic bomb, which is a cake made from wheat flour as the main ingredient